PENGARUH LITERASI MEDIA TELEVISI DAN INTERNET TERHADAP KEMAMPUAN MENGEMUKAKAN PENDAPAT PESERTA DIDIK DALAM PEMBELAJARAN IPS : Survei pada siswa SMP Negeri di Kota Bandung - Pratama, Rizki (2017)
The developments of technology in mass media should be balanced by media literacy or media intelligence. The use of television and internet among students is the effect of that phenomenon. While today, the education world realizes that it is needed to generate students who are able to solve problems, think creatively, express ideas, and like to discuss. A learning should stimulate students' participations. The ability of students in expressing opinions in learning Social Science is one of the important things. The aim of this study was to discover the description and the influence of television and internet media literacy simultaneously or partially toward the students' ability in expressing opinions in learning Social Science. The subjects involved in this study were students from Public Junior High School in Bandung. This research used survey as the method, and multiple linear regression analysis as the data analysis technique. The results of this study showed that the description of television and internet media literacy and students' ability in expressing opinion in learning Social Science was intermediate. Furthermore, television media literacy gave a positive influence toward the students' ability in expressing opinion in learning Social Science. Moreover, internet media literacy also gave a positive impact toward the students' ability in expressing opinion in learning Social Science. Simultaneously, television and internet media literacy gave a positive effect toward the students' ability in expressing opinion in learning Social Science as well. ---- Perkembangan teknologi dalam media massa harus diimbangi dengan literasi media atau kecerdasan bermedia. Penggunaan televisi dan internet dikalangan peserta didik adalah efek dari fenomena tersebut. Sedangkan dewasa ini, dunia pendidikan menyadari perlunya membentuk peserta didik yang terampil memecahkan masalah, berpikir kreatif, suka bermusyawarah, dan dapat mengkomunikasikan gagasan. Pembelajaran haruslah merangsang keikutsertaan peserta didik. Kemampuan mengemukakan pendapat peserta didik dalam pembelajaran IPS adalah salah satu hal penting. Tujuan penelitian ini untuk mengetahui gambaran dan pengaruh literasi media televisi dan internet secara simultan maupun sebagian terhadap kemampuan mengemukakan pendapat peserta didik dalam pembelajaran IPS. Subjek dalam penelitian ini adalah siswa SMP Negeri di Kota Bandung. Metode penelitian yang digunakan adalah survei serta teknik analisis data dengan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa gambaran literasi media televisi dan internet serta kemampuan mengemukakan pendapat peserta didik dalam pembelajaran IPS tergolong sedang. Selanjutnya, literasi media televisi berpengaruh positif terhadap kemampuan mengemukakan pendapat peserta didik dalam pembelajaran IPS. Lierasi media internet berpengaruh positif terhadap kemampuan mengemukakan pendapat peserta didik dalam pembelajaran IPS. Serta literasi media televisi dan internet secara simultan berpengaruh positif terhadap kemampuan mengemukakan pendapat peserta didik dalam pembelajaran IPS.